Psychological impact of COVID‐19 on hospital workers in nursing care hospitals - Seoyon Yang; Sang Gyu Kwak; Min Cheol Chang (Wiley, 2021)
Abstract Aim This study aimed to explore coronavirus disease‐related psychological stress in hospital workers in nursing care hospitals during the coronavirus disease epidemic. Design Cross‐sectional observational study. Methods A questionnaire survey was administered to hospital workers at three nursing care hospitals. Results Fifty‐four workers at three nursing care hospitals (9, 29 and 16 works) responded to our survey. Twenty‐four workers (50%) scored ≥5 on the Generalized Anxiety Disorder Scale, indicating the presence of anxiety. For the Patient Health Questionnaire‐9, six employees (11.1%) scored ≥10 scores, indicating the presence of depression. Workers who lived with other people with chronic underlying diseases showed significantly higher incidence of the presence of anxiety and depression. In binary logistic regression analysis, when living with persons with chronic underlying diseases, the risk of the presence of depression increased. Also, there was a higher incidence of depression in occupational therapists compared with physical therapists and nurses.